THE IMPORTANCE OF MARKET POWER IN BANKING: THE CASE STUDY OF THE CZECH REPUBLIC - Černohorský, Jan; Křičenská, Lucie (Varazdin Development and Entrepreneurship Agency, 2019)
Nowadays, the banking system, as a part of the financial market, is an essential element through which financial resources are redistributed in the economy. This redistribution is affected by the degree of concentration of the banking sector, or the market power of individual banks within the banking sector. Therefore the aim of this article is to analyse the importance of the market power in the banking sector, in the case of the Czech Republic. This paper is based on the research of scientific articles on the given topic and on the measurement of the market power by means of the concentration of three or five of the largest banks. These studies do not have a definite conclusion on the relationship analysed. In addition, this paper uses a correlation analysis to compare the development of the market share and earnings before taxes of six selected banks, which represent three different sizes of banks based on the Czech National Bank's classification - large banks, medium-sized banks and small banks. First, the data are tested for their normal probability distribution. If so, Pearson's correlation coefficient is used, if not Spearman's correlation coefficient is used.(Pokud ano (if so) je tady nejasné. Můj návrh: If the test is positive, Pearson's correlation coefficient is used, if not Spearman's correlation coefficient is used. The volume of the assets is used to measure the market share. It concludes that a relationship between market share and profit development does not exist. However, this conclusion is not unambiguous because in some cases the correlation has been confirmed, both in a positive and a negative sense. The discussion then outlines factors that are likely to result in the more ambiguous conclusions.
Význam tržní síly v bankovnictví: případová studie České republiky
Keywords: banking, concentration, earninsg before taxes, market power; bankovnictví, koncentrace, zisk před zdaněním, tržní síla